Designing a blueprint for coral reef survival. (May 2021) - Kleypas, Joan; Allemand, Denis; Anthony, Ken; Baker, Andrew C.; Beck, Michael W.; Hale, Lynne Zeitlin; Hilmi, Nathalie; Hoegh-Guldberg, Ove; Hughes, Terry; Kaufman, Les; Kayanne, Hajime; Magnan, Alexandre K.; et al.
Abstract: Maintaining coral reef ecosystems is a social imperative, because so many people depend on coral reefs for food production, shoreline protection, and livelihoods. The survival of reefs this century, however, is threatened by the mounting effects of climate change. Climate mitigation is the foremost and essential action to prevent coral reef ecosystem collapse. Without it, reefs will become extremely diminished within the next 20–30 years. Even with strong climate mitigation, however, existing conservation measures such as marine protected areas and fisheries management are no longer sufficient to sustain the ecosystem and many additional and innovative actions to increase reef resilience must also be taken. In this paper we assess the suite of protections and actions in terms of their potential to be effective according to a set of criteria that include effectiveness, readiness, co-benefits and disbenefits. Even with the best scientific innovation, saving coral reefs will require a well-funded, well-designed, and rapidly executed strategy with political and social commitments at the level of other grand challenges. Highlights: Coral reef ecosystems will continue to decline significantly and globally. Climate mitigation is an essential but insufficient action to conserve reefs. Coral adaptation to warming will only be effective under low emission scenarios. Reef protection and innovations to increase coral resilience need rapid development. Saving coral reefs requires effort and funding on par with other grand challenges.